2015
DOI: 10.1155/2015/676930
|View full text |Cite|
|
Sign up to set email alerts
|

A Case of In-Bore Transperineal MRI-Guided Prostate Biopsy of a Patient with Ileal Pouch-Anal Anastomosis

Abstract: Ulcerative colitis (UC) is an inflammatory disease that specifically affects the colon. Ulcerative colitis is primarily treated medically and refractory disease is treated with proctocolectomy and ileal pouch-anal anastomosis (IPAA). Gastroenterologists advise against digital rectal exams, pelvic radiation therapy, and transrectal ultrasound (TRUS) biopsies of the prostates of ileal pouch-anal anastomosis patients. Any form of pouch manipulation can lead to severe bleeding, inflammation, and pain. Urologists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Although there is no clear correlation between IBD and prostate cancer, it has been shown that men with UC ulcerative colitis have a higher risk of developing prostate cancer [ 10 ]. While some IBD patients with ileal pouch-anal anastomosis can get transperineal biopsy with ultrasound guidance through the ileal pouch [ 11 , 12 ], it may not always be feasible owing to strictures at the anastomosis. Ultrasound-guided or in-bore transperineal prostate biopsy is an option in this setting but can be challenging due to complexity of the procedure, excessive fibrosis, and limited availability as well as requirement of general anesthesia in case of in-bore transperineal biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no clear correlation between IBD and prostate cancer, it has been shown that men with UC ulcerative colitis have a higher risk of developing prostate cancer [ 10 ]. While some IBD patients with ileal pouch-anal anastomosis can get transperineal biopsy with ultrasound guidance through the ileal pouch [ 11 , 12 ], it may not always be feasible owing to strictures at the anastomosis. Ultrasound-guided or in-bore transperineal prostate biopsy is an option in this setting but can be challenging due to complexity of the procedure, excessive fibrosis, and limited availability as well as requirement of general anesthesia in case of in-bore transperineal biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high precision, in-bore MRI targeted biopsy is not routinely used because it is costly, requires a lot of personnel time, specialized MRI compatible equipment, and discomfort from prone positioning. It may be particularly useful for patients in which TRUS may not be possible such as post-abdominoperineal resection (11). …”
Section: Introductionmentioning
confidence: 99%
“…In the article titled “A Case of In-Bore Transperineal MRI-Guided Prostate Biopsy of a Patient with Ileal Pouch-Anal Anastomosis,” [ 1 ] the name of the ninth author was given incorrectly as Brad J. Wood.…”
mentioning
confidence: 99%